Antifungal Activity of Seeds of Hyoscyamus niger L. (Henbane) Against Some Clinically Relevant Fungal Pathogens - Dulger, Basaran; Hacioglu, Nurcihan; S. Goncu, Beyza; Gucin, Fahrettin (Asian Journal of Chemistry, 2010)
The methanolic extracts obtained from the seeds of Hyoscyamus niger L. (Solanaceae) used as traditional medicine in Turkey were investigated for their ability to inhibit clinically relevant fungal pathogens as six Candida species (C. albicans ATCC 10231, C. tropicalis ATCC 13808, C. guilliermondii ATCC 6260, C. krusei ATCC 20298, C. glabrata ATCC 2001 and C. parapsilosis ATCC 22019) and two Cryptococcus species (C. neoformans ATCC 90112 and C. laurentii ATCC 34142) by microbroth dilution method. The plant displayed activity against all fungal cultures tested. The extracts possessed a strong antifungal potency. Greater activity was observed against both Cryptococcus species, with MIC values of 15 μg/mL.